Perceived Effectiveness of Public Health Unit Partnerships With Faith-Based and Other Community-Based Organizations to Promote COVID-19 Vaccination Among Ethnoracial Communities - Melodie Yunju Song; Denessia Blake-Hepburn; Monali Varia; Elizabeth Estey Noad; Nazia Peer; Barry Pakes; Barry Pakes; Shaza A. Fadel; Sara Allin; Anushka Ataullahjan; Erica Di Ruggiero; Erica Di Ruggiero (International Journal of Public Health, 2024)
ObjectivesThe objective of this study was to explore how Ontario Public Health Units (PHUs) partnered with faith-based organizations (FBOs) and other community-based organizations (CBOs) to promote COVID-19 vaccination among ethnoracial groups made structurally vulnerable during the pandemic, and to understand how PHUs perceive the effectiveness of these partnerships with these organizations.MethodsBetween June to December 2022, we distributed a cross-sectional survey to 34 PHUs in Ontario to explore how PHUs were engaging and partnering with FBOs and CBOs.ResultsResponses were received from 28 of 34 (82.5%) public health units. Across Ontario, 23 (82.1%) respondent PHUs worked with FBOs during the COVID-19 vaccine rollout with activities ranging from informing FBOs of vaccine availability, to using places of worship as sites for vaccine administration and co-creating educational materials on immunization that were faith- and culturally sensitive.ConclusionFBOs can be a valuable community partner as PHUs work to increase the reach and uptake of public health interventions. Ongoing monitoring and evaluation of the impact of FBO engagement on vaccine confidence and uptake among ethnoracial communities is needed to inform future community engaged vaccine programming in Ontario.